Ewi Atenudenu Laaarin Awon Igbomina. - Awotayo, Atolani (Obafemi Awolowo University, 2014)
The present study fills a gap in the study of the Yoruba Oral Literature by providing a systematic survey and characterisation of the poetic genres among the Igbomina people. The study classifies the poetic genres among; the Igbomina with respect to their provenance and functions in correlation with socio-economic groups.